Reaching influential early adopters effectively in Finland : Rock Science – new generation board game - Ikonen, Onni (My University, 2014)
Innovations diffuse at different speed among the members of a social system through various communication channels. The group of early adopters can be seen as the most influential reference group for majority of people to base their innovation adoption decisions on. Thus, the early adopters can often accelerate the diffusion of innovations. The purpose of this research is to discover means of diffusion for an innovative product in Finnish market through the influential early adopters in respect to the characteristics of the case product. The purpose of the research can be achieved through the following sub objectives:  Who are the potential early adopters for the case product and why?  How the potential early adopters of the case product should be communicated with?  What would be the expectations, preferences, and experiences of the early adopters of the case product? The case product examined in this research is a new board game called Rock Science which is considered to be incremental innovation bringing board gaming and hard rock music together in a new way. The research was conducted in two different parts using both qualitative and quantitative research methods. This mixed method research began with expert interviews of six music industry experts. The information gathered from the interviews enabled researcher to compose the questionnaire for the quantitative part of the study. Internet survey that was sent out resulted with a sample of 97 responses from the targeted population. The key findings of the study suggest that (1) the potential early adopters for the case product are more likely to be young adults from the capital city area with great interest in rock music, (2) the early adopters can be reached effectively through credible online sources of information, and (3) the respondents overall product feedback is highly positive, except in the case of quality-price ratio of the product. This research indicates that more effective diffusion of Rock Science board game in Finland can be reached through (1) strategic alliances with music industry and media partnerships, (2) pricing adjustments, (3) use of supporting game formats, and (4) innovative use of various social media channels.